Examining the agricultural producer identity: utilising the collective occupational identity construct to create a typology and profile of rural landholders in Victoria, Australia. Issue 4 (3rd April 2017) - Groth, Theresa M.; Curtis, Allan; Mendham, Emily; Toman, Eric
Abstract : Multifunctional rural landscapes are often characterised by contrasting values, land uses and land management practices of rural property owners. It seems these trends are, in part, an expression of rural landholder's identification as farmers. Existing typologies of rural landholders seldom take into account occupational identity. Research discussed in this paper addresses that gap. The objective was to apply the collective occupational identity construct to address the challenges of profiling rural landholders and test its effectiveness at distinguishing between different types of landholders. A 12-item scale was used to explore the extent rural landholders in south-eastern Australia held an agricultural producer identity. Cluster analysis resulted in the creation of four clusters of rural landholders with distinctive characteristics, suggesting the approach can provide researchers with a theoretically sound construct and practitioners with a useful tool as they attempt to better understand and engage rural landholders in sustainable agriculture.